(untitled) (Eureka Journal of Humanities and Social Research, 2026)
Pedagogical communication is the foundation of effective teacher-student engagement. However, students may experience a variety of psychological issues as a result of poor or inappropriate classroom communication. This article looks at the main forms of ineffective pedagogical communication and how they impact students’ self-esteem, emotional stability, and study motivation. The study also highlights how teachers’ empathy, communication abilities, and the overall psychological climate of the classroom affect students’ mental health. The findings demonstrate that mistrust, fear, a reduction in self-expression, and a decline in autonomous thought are frequently brought on by inappropriate communication, which includes threats, indifference, humiliation, or neglect. Thus, ensuring successful and psychologically safe teaching requires fostering a positive learning environment in the classroom, enhancing emotional intelligence, and developing teachers’ communication cultures.